Analisis Diversifikasi Produk Terhadap Keputusan Pembelian Pada Rumah Makan Seruit Hj. Yohana Kota Metro - Rizki, Muhammad; Baskoro, Ery (Jurnal Manajemen DIVERSIFIKASI, 2022)
Muhammad Rizki, 2021 “Analysis of Product Diversification on Purchase Decisions at the Seruit Hj. Yohana Metro City". Faculty of Economics and Business, University of Muhammadiyah Metro. Supervisor: (1) Ery Baskoro, S. E,. M. M and Supervisor (2) Yateno, S.E., M. M. This study aims to determine the analysis of product diversification on purchasing decisions at the Seruit Hj Restaurant. Yohana Metro City. By distributing questionnaires in the form of questions about product variety, product size and product shape towards purchasing decisions. Then processed with SPSS version 22 with the classical assumption test approach with the methods of normality, linearity, homogeneity. This study uses quantitative methods with multiple linear regression analysis, partial test, F test, determination to determine product variety, product size and product shape on purchasing decisions. The results showed that simultaneously product variety, product size and product form Partial research showed that product variety had a positive and significant effect, product size had a positive and significant effect and product form had a positive and significant effect on purchasing decisions. Keywords: product variety, product size, product shape, purchase decision